Synthesis and Characterizations of Nanocrystalline Na and Al Codoped Nio Thin Films - Benramache, Said; Guezzoun, Hanane; Benhaoua, Boubaker (International Journal of Integrated Engineering, 2020)
In the present work, Na and Al codoped NiO thin films were successfully deposited on a glass substrate by spray pneumatic method. The effect of Al concentration on optical, structural and electrical properties was studied. The transmission spectra show that the Na and Al codoped NiO thin films have good optical transparency in the visible region. The optical band gap energy increased after co-doping by Al to maximum value was 3.926 eV for 2 % Al. The minimum value of Urbach energy was obtained at high Al concentration it is 0.319 eV for 3 % Al. The Na and Al codoped NiO films have a minimum electrical resistance obtained for 1 % Al. XRD patterns of the Na and Al codoped NiO thin films indicating that the Na and Al codoped NiO thin films have a cubic structure of NiO phase.